(untitled) (Sir Salimullah Medical College Journal, 2026)
Bangladesh is undergoing a complex epidemiological transition characterized by a growing burden of infectious diseases and a rapidly growing number of noncommunicable diseases (NCDs).This dual challenge has a significant impact on the country’s healthcare system and public health priorities. Sir Salimullah Med Coll J 2025; 33: 132-134